(untitled) (Research, Society and Development, 2022)
Among the various cardiovascular diseases, the Acute Myocardial Infarction stands out, which is a lesion that affects the heart muscle, caused by an inadequate decrease in the supply of nutrients and oxygen, inducing blood flow obstruction, which can develop tissue necrosis. The nurse is the professional qualified to perform various actions and care for patients with AMI. Therefore, the research aims to describe the associated factors and nursing care for patients with AMI. This is an exploratory, qualitative, and descriptive study, using as a technique the Integrative Literature Review and the PICO strategy to form the problem question. The research was carried out between March and May 2022, in the following databases: BDENF, MEDLINE and LILACS. The search was performed by joining three descriptors, crossed with the Boolean operator “AND”: “Myocardial Infarction, Cardiovascular Diseases, Nursing Care”. A total of 1,393 articles were found. By adding the inclusion and exclusion criteria, this number was reduced to 51. After analysis, 13 surveys were selected. The main care for the patient affected by AMI is comfort in the ICU bed, reducing the levels of anxiety of this patient in the face of a serious condition. The actions performed by nurses are extremely important in the face of care directed to patients with AMI. Therefore, it is necessary that the research can serve as a subsidy to guide other publications, collaborating for the dissemination of scientific knowledge.